Uma análise discursiva das mulheres de/em Chico Buarque - Vasconcelos, Grace Terra Santos Agra (2014)
Chico Buarque s songs became objects of study in academy because they explain the political context of the time. Therewith, the composer s songs began to be exploited, also, in Discourse Analysis studies field. In this perspective, the present work expounds the analysis of song composed during the period of military coup in Brazil, having as theoretical ground, French Discourse Analysis, founded by Michel Pêcheux, in 1969, in France and developed in Brazil by Eni Orlandi and her followers. This work has as main purpose analyze both political and poetic discourse of the songs that Chico Buarque sings as in the place of women, composed during the Brazilian military government. Specifically, we intend to investigate the discursive formations and ideological of women in a song by Chico Buarque, besides identifying the interspeech of/about the woman in the song's composer. At the same time, we aim to understand the discursive psychology present in the discourse of/about women, but also highlight the position of subject-woman in songs by Chico Buarque. This research makes an analysis of the discourse of/about women in composer s music, considering the discourse of resistance to the military coup approached by Chico Buarque. The aim is, thus, to understand the meaning effects of this discourse through the unsaid existent in this silence discourse. For this purpose, five songs were selected for analysis, composed between the years 1964 to 1979, take into consideration the conditions of discourse production, based on the theories and analytical procedures of DA. From this viewpoint, it is observed that the announcer express the place of women, occupying different positions, from the submissive woman to the forefront one, all immersed in the ideology of a society that lived oppressed by the military dictatorship. In the selected corpus discursive analysis, the subject-woman discursive formations slide from the submission to independence. The conditions of production are the dictatorship, which silencing was broken in the arts and the works metaphorical effect said what the military subject could not hear. In the censorship and the resistance, the women in Chico Buarque showed the rupture strength of a say. The discursive analysis fortify the social mores of an initial era, where the patriarchalism was present more strongly, in contrast to other, a marked feminism. The study was concluded, evidencing Chico Buarque s poetic/political discourse, which the female subject is approached in the compositions, marked by discursive/ideological formations politics, social and cultural representatives of the military dictatorship.